5.9.38 Problems 3701 to 3800

Table 5.703: First order ode linear in derivative

#

ODE

Mathematica

Maple

10088

\[ {}y^{\prime }-f \left (x \right ) \left (y-g \left (x \right )\right ) \sqrt {\left (y-a \right ) \left (y-b \right )} = 0 \]

10089

\[ {}y^{\prime }-{\mathrm e}^{x -y}+{\mathrm e}^{x} = 0 \]

10090

\[ {}y^{\prime }-a \cos \left (y\right )+b = 0 \]

10091

\[ {}y^{\prime }-\cos \left (b x +a y\right ) = 0 \]

10092

\[ {}y^{\prime }+a \sin \left (\alpha y+\beta x \right )+b = 0 \]

10093

\[ {}y^{\prime }+f \left (x \right ) \cos \left (a y\right )+g \left (x \right ) \sin \left (a y\right )+h \left (x \right ) = 0 \]

10094

\[ {}y^{\prime }+f \left (x \right ) \sin \left (y\right )+\left (1-f^{\prime }\left (x \right )\right ) \cos \left (y\right )-f^{\prime }\left (x \right )-1 = 0 \]

10095

\[ {}y^{\prime }+2 \tan \left (y\right ) \tan \left (x \right )-1 = 0 \]

10096

\[ {}y^{\prime }-a \left (1+\tan \left (y\right )^{2}\right )+\tan \left (y\right ) \tan \left (x \right ) = 0 \]

10097

\[ {}y^{\prime }-\tan \left (x y\right ) = 0 \]

10098

\[ {}y^{\prime }-f \left (a x +b y\right ) = 0 \]

10099

\[ {}y^{\prime }-x^{a -1} y^{1-b} f \left (\frac {x^{a}}{a}+\frac {y^{b}}{b}\right ) = 0 \]

10100

\[ {}y^{\prime }-\frac {y-x f \left (x^{2}+y^{2} a \right )}{x +a y f \left (x^{2}+y^{2} a \right )} = 0 \]

10101

\[ {}y^{\prime }-\frac {y a f \left (x^{c} y\right )+c \,x^{a} y^{b}}{x b f \left (x^{c} y\right )-x^{a} y^{b}} = 0 \]

10102

\[ {}2 y^{\prime }-3 y^{2}-4 a y-b -c \,{\mathrm e}^{-2 a x} = 0 \]

10103

\[ {}x y^{\prime }-\sqrt {a^{2}-x^{2}} = 0 \]

10104

\[ {}x y^{\prime }+y-x \sin \left (x \right ) = 0 \]

10105

\[ {}x y^{\prime }-y-\frac {x}{\ln \left (x \right )} = 0 \]

10106

\[ {}x y^{\prime }-y-x^{2} \sin \left (x \right ) = 0 \]

10107

\[ {}x y^{\prime }-y-\frac {x \cos \left (\ln \left (\ln \left (x \right )\right )\right )}{\ln \left (x \right )} = 0 \]

10108

\[ {}x y^{\prime }+a y+b \,x^{n} = 0 \]

10109

\[ {}x y^{\prime }+y^{2}+x^{2} = 0 \]

10110

\[ {}x y^{\prime }-y^{2}+1 = 0 \]

10111

\[ {}x y^{\prime }+y^{2} a -y+b \,x^{2} = 0 \]

10112

\[ {}x y^{\prime }+y^{2} a -b y+c \,x^{2 b} = 0 \]

10113

\[ {}x y^{\prime }+y^{2} a -b y-c \,x^{\beta } = 0 \]

10114

\[ {}x y^{\prime }+x y^{2}+a = 0 \]

10115

\[ {}x y^{\prime }+x y^{2}-y = 0 \]

10116

\[ {}x y^{\prime }+x y^{2}-y-a \,x^{3} = 0 \]

10117

\[ {}x y^{\prime }+x y^{2}-\left (2 x^{2}+1\right ) y-x^{3} = 0 \]

10118

\[ {}x y^{\prime }+a x y^{2}+2 y+b x = 0 \]

10119

\[ {}x y^{\prime }+a x y^{2}+b y+c x +d = 0 \]

10120

\[ {}x y^{\prime }+x^{a} y^{2}+\frac {\left (a -b \right ) y}{2}+x^{b} = 0 \]

10121

\[ {}x y^{\prime }+a \,x^{\alpha } y^{2}+b y-c \,x^{\beta } = 0 \]

10122

\[ {}x y^{\prime }-y^{2} \ln \left (x \right )+y = 0 \]

10123

\[ {}x y^{\prime }-y \left (-1+2 y \ln \left (x \right )\right ) = 0 \]

10124

\[ {}x y^{\prime }+f \left (x \right ) \left (y^{2}-x^{2}\right )-y = 0 \]

10125

\[ {}x y^{\prime }+y^{3}+3 x y^{2} = 0 \]

10126

\[ {}x y^{\prime }-\sqrt {x^{2}+y^{2}}-y = 0 \]

10127

\[ {}x y^{\prime }+a \sqrt {x^{2}+y^{2}}-y = 0 \]

10128

\[ {}x y^{\prime }-x \sqrt {x^{2}+y^{2}}-y = 0 \]

10129

\[ {}x y^{\prime }-x \left (y-x \right ) \sqrt {x^{2}+y^{2}}-y = 0 \]

10130

\[ {}x y^{\prime }-x \,{\mathrm e}^{\frac {y}{x}}-y-x = 0 \]

10131

\[ {}x y^{\prime }-y \ln \left (y\right ) = 0 \]

10132

\[ {}x y^{\prime }-y \left (\ln \left (x y\right )-1\right ) = 0 \]

10133

\[ {}x y^{\prime }-y \left (x \ln \left (\frac {x^{2}}{y}\right )+2\right ) = 0 \]

10134

\[ {}x y^{\prime }-\sin \left (x -y\right ) = 0 \]

10135

\[ {}x y^{\prime }+\left (\sin \left (y\right )-3 x^{2} \cos \left (y\right )\right ) \cos \left (y\right ) = 0 \]

10136

\[ {}x y^{\prime }-\sin \left (\frac {y}{x}\right ) x -y = 0 \]

10137

\[ {}x y^{\prime }+x \cos \left (\frac {y}{x}\right )-y+x = 0 \]

10138

\[ {}x y^{\prime }+x \tan \left (\frac {y}{x}\right )-y = 0 \]

10139

\[ {}x y^{\prime }-y f \left (x y\right ) = 0 \]

10140

\[ {}x y^{\prime }-y f \left (x^{a} y^{b}\right ) = 0 \]

10141

\[ {}x y^{\prime }+a y-f \left (x \right ) g \left (x^{a} y\right ) = 0 \]

10142

\[ {}\left (1+x \right ) y^{\prime }+y \left (y-x \right ) = 0 \]

10143

\[ {}2 x y^{\prime }-y-2 x^{3} = 0 \]

10144

\[ {}\left (2 x +1\right ) y^{\prime }-4 \,{\mathrm e}^{-y}+2 = 0 \]

10145

\[ {}3 x y^{\prime }-3 x \ln \left (x \right ) y^{4}-y = 0 \]

10146

\[ {}x^{2} y^{\prime }+y-x = 0 \]

10147

\[ {}x^{2} y^{\prime }-y+x^{2} {\mathrm e}^{x -\frac {1}{x}} = 0 \]

10148

\[ {}x^{2} y^{\prime }-\left (x -1\right ) y = 0 \]

10149

\[ {}x^{2} y^{\prime }+y^{2}+x y+x^{2} = 0 \]

10150

\[ {}x^{2} y^{\prime }-y^{2}-x y = 0 \]

10151

\[ {}x^{2} y^{\prime }-y^{2}-x y-x^{2} = 0 \]

10152

\[ {}x^{2} \left (y^{\prime }+y^{2}\right )+a \,x^{k}-b \left (b -1\right ) = 0 \]

10153

\[ {}x^{2} \left (y^{\prime }+y^{2}\right )+4 x y+2 = 0 \]

10154

\[ {}x^{2} \left (y^{\prime }+y^{2}\right )+a x y+b = 0 \]

10155

\[ {}x^{2} \left (y^{\prime }-y^{2}\right )-a \,x^{2} y+a x +2 = 0 \]

10156

\[ {}x^{2} \left (y^{\prime }+y^{2} a \right )-b = 0 \]

10157

\[ {}x^{2} \left (y^{\prime }+y^{2} a \right )+b \,x^{\alpha }+c = 0 \]

10158

\[ {}x^{2} y^{\prime }+a y^{3}-a \,x^{2} y^{2} = 0 \]

10159

\[ {}x^{2} y^{\prime }+x y^{3}+y^{2} a = 0 \]

10160

\[ {}x^{2} y^{\prime }+a \,x^{2} y^{3}+b y^{2} = 0 \]

10161

\[ {}\left (x^{2}+1\right ) y^{\prime }+x y-1 = 0 \]

10162

\[ {}\left (x^{2}+1\right ) y^{\prime }+x y-x \left (x^{2}+1\right ) = 0 \]

10163

\[ {}\left (x^{2}+1\right ) y^{\prime }+2 x y-2 x^{2} = 0 \]

10164

\[ {}\left (x^{2}+1\right ) y^{\prime }+\left (1+y^{2}\right ) \left (2 x y-1\right ) = 0 \]

10165

\[ {}\left (x^{2}+1\right ) y^{\prime }+x \sin \left (y\right ) \cos \left (y\right )-x \left (x^{2}+1\right ) \cos \left (y\right )^{2} = 0 \]

10166

\[ {}\left (x^{2}-1\right ) y^{\prime }-x y+a = 0 \]

10167

\[ {}\left (x^{2}-1\right ) y^{\prime }+2 x y-\cos \left (x \right ) = 0 \]

10168

\[ {}\left (x^{2}-1\right ) y^{\prime }+y^{2}-2 x y+1 = 0 \]

10169

\[ {}\left (x^{2}-1\right ) y^{\prime }-y \left (y-x \right ) = 0 \]

10170

\[ {}\left (x^{2}-1\right ) y^{\prime }+a \left (y^{2}-2 x y+1\right ) = 0 \]

10171

\[ {}\left (x^{2}-1\right ) y^{\prime }+a x y^{2}+x y = 0 \]

10172

\[ {}\left (x^{2}-1\right ) y^{\prime }-2 x y \ln \left (y\right ) = 0 \]

10173

\[ {}\left (x^{2}-4\right ) y^{\prime }+\left (x +2\right ) y^{2}-4 y = 0 \]

10174

\[ {}\left (x^{2}-5 x +6\right ) y^{\prime }+3 x y-8 y+x^{2} = 0 \]

10175

\[ {}\left (x -a \right ) \left (x -b \right ) y^{\prime }+y^{2}+k \left (y+x -a \right ) \left (y+x -b \right ) = 0 \]

10176

\[ {}2 x^{2} y^{\prime }-2 y^{2}-x y+2 x \,a^{2} = 0 \]

10177

\[ {}2 x^{2} y^{\prime }-2 y^{2}-3 x y+2 x \,a^{2} = 0 \]

10178

\[ {}x \left (2 x -1\right ) y^{\prime }+y^{2}-\left (4 x +1\right ) y+4 x = 0 \]

10179

\[ {}2 x \left (x -1\right ) y^{\prime }+\left (x -1\right ) y^{2}-x = 0 \]

10180

\[ {}3 x^{2} y^{\prime }-7 y^{2}-3 x y-x^{2} = 0 \]

10181

\[ {}3 \left (x^{2}-4\right ) y^{\prime }+y^{2}-x y-3 = 0 \]

10182

\[ {}\left (a x +b \right )^{2} y^{\prime }+\left (a x +b \right ) y^{3}+c y^{2} = 0 \]

10183

\[ {}x^{3} y^{\prime }-y^{2}-x^{4} = 0 \]

10184

\[ {}x^{3} y^{\prime }-y^{2}-x^{2} y = 0 \]

10185

\[ {}x^{3} y^{\prime }-y^{2} x^{4}+x^{2} y+20 = 0 \]

10186

\[ {}x^{3} y^{\prime }-y^{2} x^{6}-\left (2 x -3\right ) x^{2} y+3 = 0 \]

10187

\[ {}x \left (x^{2}+1\right ) y^{\prime }+x^{2} y = 0 \]